Combination of Forward Chaining and Certainty Factor Methods In An Expert System for Diagnosis of Cattle Diseases - Ramadan, Chafiz; Santoso, Heri; Irawan, Muhammad Dedi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
Cows are one of the most widely cultivated livestock animals in Indonesia, especially in the Asahan district alone, according to data from Asahan in Figures for 2022, in Asahan District in 2021 there will be 146,511 heads spread across 25 sub-districts. Cow disease is no longer a strange thing for livestock breeders. The symptoms that appear in cattle must be known as soon as possible before the disease appears with a ferocity that will cause the risk of death in cattle. death in Mr Poniman's cattle. Due to tympanic disease (bloating), at the time of this incident there were still few cows and people did not know how to treat it, so the cows eventually died with enlarged stomachs. With the availability of technology, the author built an expert system for diagnosing cattle diseases that can diagnose cattle diseases and provide treatment suggestions, both medical and natural, using the forward chaining method and certainty factor. Forward chaining first selects facts that are appropriate to the problem that is occurring, and the certainty factor will determine the result of the percentage of confidence of an expert. This system was built based on a website.